Dimeric dipeptide mimetics of BDNF loop 4 are potential antidepressants with novel mechanisms of action - T. A. Gudasheva; P. Yu. Povarnina; A. V. Tarasyuk; V. P. Zherdev; A. D. Durnev (Фармакокинетика и Фармакодинамика)
This review covers original research focused on the design, synthesis, and pharmacological evaluation of an innovative dimeric dipeptide mimetic of brain-derived neurotrophic factor (BDNF) loop 4 bis-(N-monosuccinyl-L-seryl-L-lysine) hexamethylenediamide (GSB-106). Developed using a proprietary approach for creating low-molecular-weight neurotrophin mimetics, GSB-106 displayed marked antidepressant-like activity following systemic and oral administration. The article details its pharmacological properties in vitro and in vivo, mechanism of action, development of a tablet form of the dipeptide, and findings from toxicological and pharmacokinetic studies.